Correlation between weekly working time and burnout syndrome among anesthesiologists of Maceió-AL - Barbosa,Fabiano Timbó (2017)
Abstract Background and objective: The current jobs are insufficient to determine the causative agent, as well as to identify characteristic high risk profiles for BS, leaving a clear need for more studies to this end. This study objective was to evaluate the correlation between weekly workload and BS dimensions. Methods: An observational, descriptive, cross-sectional study performed with 43 anesthesiologists from Maceió-AL, with the application of Maslach Burnout Inventory (MBI) forms. Pearson's correlation coefficient r was used for the three dimensions and a 95% confidence interval for the prevalence of burnout syndrome and high scores in all three dimensions. Results: Among the studied physicians, 51.16% were male and the average age was 49.82 ± 12.05 years. For physicians who have been diagnosed with BS through the MBI, the average weekly working time 69.27 ± 22.39 h. The high level of frequency in at least one of the three dimensions was found in 67.44% of physicians, with this percentage being considered diagnostic for burnout syndrome in this population. Conclusion: This study showed no correlation between the weekly working time and the BS dimensions in this population.